Diseño de una arquitectura que facilite la interoperabilidad semántica entre componentes autónomos dentro de la industria 4.0 (2017)
"The advance of IoT solutions and the incursion of these solutions into the industry have generated the so-called fourth industrial revolution or industry 4.0. The vision of this establishes the need to incorporate a network of Cyber-Physical Systems (CPS) that are able to exchange information. However, accelerated advancement in technologies has generated heterogeneity of standards and solutions for the industry, making integration difficult for a system in the industry. This paper proposes a software architecture, based on the OpenMTC (Machine Type Communication) platform and ontologies transformations, ensuring semantic and network interoperability between components. Likewise, the key points of the architecture are identified and the proposal is evaluated based on existing solutions." -- Tomado del Formato de Documento de Grado.